2006
DOI: 10.1590/s0100-83582006000300014
|View full text |Cite
|
Sign up to set email alerts
|

Intoxicação de eucalipto submetido à deriva simulada de diferentes herbicidas

Abstract: RESUMO -Além do glyphosate, amplamente usado, outros herbicidas, como o triclopyr e o carfentrazone-ethyl, apresentam potencial de uso na eucaliptocultura. Entretanto, a não-seletividade destes herbicidas ao eucalipto pode levar à intoxicação da cultura, caso haja contato das folhas com a calda aplicada.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 9 publications
1
5
0
2
Order By: Relevance
“…Motavalli et al and Kowalchuk et al found no conclusive evidence that GRS and other transgenic crops which have been used in many cropping situations in many climates and soil types over the past 14 years have had any significant effect on nutrient transformations by microbes. No effects were detected from glyphosate on earthworms (Eisenia fetida Savigny) in Brazil, on other plants from glyphosate exudation from roots of Brachiaria decumbens Stapf or drift, , and on the entomopathogenic fungus Metarhizium anisopliae (Metsch. ), important in Brazil for insect biocontrol .…”
Section: Effects On Soil Biota and Microorganismsmentioning
confidence: 99%
“…Motavalli et al and Kowalchuk et al found no conclusive evidence that GRS and other transgenic crops which have been used in many cropping situations in many climates and soil types over the past 14 years have had any significant effect on nutrient transformations by microbes. No effects were detected from glyphosate on earthworms (Eisenia fetida Savigny) in Brazil, on other plants from glyphosate exudation from roots of Brachiaria decumbens Stapf or drift, , and on the entomopathogenic fungus Metarhizium anisopliae (Metsch. ), important in Brazil for insect biocontrol .…”
Section: Effects On Soil Biota and Microorganismsmentioning
confidence: 99%
“…Similar results were found by Brandão et al (2014), who observed reduction of up to 50% in root dry mass of açaí plants that received application of herbicides in 3-leaf stage. Tuffi-Santos et al (2006) found a decrease of approximately 60% in the root dry mass of Eucalyptus under application of 172 g ha -1 of glyphosate.…”
Section: ∆Cmentioning
confidence: 91%
“…These results demonstrate that both molecules were less aggressive to eucalyptus compared to clomazone (Gamit 500 ). Regarding the diameter, Tuffi Santos, L. Ferreira, F. Ferreira, Duarte, and Tiburcio (2006), and Tiburcio, F. Ferreira, L. Ferreira, M. Machado, and A. Machado (2012) also found no significant difference for various herbicides evaluated, indicating that this characteristic is not affected in periods of evaluation equal to or lower than 90 DAP, probably because it is a perennial crop and presents a slower development.…”
Section: St Experiment: Selectivity Of Graminicides To Eucalyptusmentioning
confidence: 96%